A Preliminary Component Analysis of Self-Regulated Strategy Development for Persuasive Writing in Grades 5 to 7 in British Columbia. (March 2019) - Geres-Smith, Rhonda; Mercer, Sterett H.; Archambault, Catherine; Bartfai, Jamie M.
Self-regulated strategy development (SRSD) has extensive evidence of improving student writing; however, few studies have investigated the relative importance of specific self-regulation components in SRSD. Twelve students in Grades 5 to 7 were assigned to one of two, 5-week SRSD conditions for persuasive writing that differed in instruction on the use of self-statements. No differences in outcomes were found between SRSD conditions, but large gains in writing quality, composition duration, and writing self-efficacy were found in both conditions. Although limited by not including a no-intervention comparison condition, the observed gains were typical of effect sizes reported in meta-analyses of SRSD and provide some additional evidence of replication in independent research teams and in a Canadian context.